Design of a vibrometer with Arduino and Simulink - Altamirano-Santillán, Edwin Vinicio (2016)
The objective of this work is to explain the design, simulation and implementation of a vibrometer that could measure the oscillatory frequency of a particular structure in a wide range. The possibility of measuring a large frequency range is obtained with a simple change of the model in Simulink. The design of the electronic scheme proposed is implemented using the Arduino platform, planned and simulated with the Simulink tool of MATLAB, with the advantages that this philosophy reports in the design. This results in a low-cost electronic scheme that utilizes a magnetic switch as a very simple and cheap magnetic transducer. Considering that the scheme utilizes a low percentage of the Arduino, this might be used in other acquisitions and processing of a system.